2007
DOI: 10.1055/s-2007-965431
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sulfur Nutrition on Plant Glucosinolate Content: Physiology and Molecular Mechanisms

Abstract: Glucosinolates are sulfur-rich plant metabolites of the order Brassicales that function in the defense of plants against pests and pathogens. They are also important in human society as flavor components, cancer-prevention agents, and crop biofumigants. Since glucosinolates may represent up to 30 % of the total sulfur content of plant organs, their accumulation should depend intimately on the sulfur status of the entire plant. Here we review the literature on how sulfur supply affects glucosinolate content. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
233
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(247 citation statements)
references
References 74 publications
8
233
3
3
Order By: Relevance
“…In sprouts, GLS concentration remained almost constant over time and similarly to the roots they benefited from the fertilisation. It has been reported that sulphur fertilisation allowed an increase in GLS concentration in most cases, even by over 10 times, suggesting that there are substantial opportunities to manipulate the GLS concentration in plants to enhance their organoleptic and health properties, or their value as biofumigants (Falk et al, 2007). On wasabi, whose flavour, as for horseradish comes from the liberation of the allyl-isothiocyanate (AITC) by the hydrolysis of precursor SIN, Sultana et al (2002) found that fertilisation with ammonium sulphate produced the highest-quality rhizomes with an increase by 72% in AITC yield, while nitrogen fertiliser alone reduced the AITC yield by up to 15%, showing the importance of sulphur in improving the AITC concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In sprouts, GLS concentration remained almost constant over time and similarly to the roots they benefited from the fertilisation. It has been reported that sulphur fertilisation allowed an increase in GLS concentration in most cases, even by over 10 times, suggesting that there are substantial opportunities to manipulate the GLS concentration in plants to enhance their organoleptic and health properties, or their value as biofumigants (Falk et al, 2007). On wasabi, whose flavour, as for horseradish comes from the liberation of the allyl-isothiocyanate (AITC) by the hydrolysis of precursor SIN, Sultana et al (2002) found that fertilisation with ammonium sulphate produced the highest-quality rhizomes with an increase by 72% in AITC yield, while nitrogen fertiliser alone reduced the AITC yield by up to 15%, showing the importance of sulphur in improving the AITC concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Sulforaphane is a sulfur-containing isothiocyanates that is hydrolyzed from glucosinolates by myrosinase. Sulforaphane production decreased with seed growth because of degradation of glucosinolates to support the formation of other sulfur-containing compounds, particularly under lowsulfur conditions (Falk et al 2007). Much of the reduction in concentration may be simply a result of plant expansion, which diluted the compounds and decreased their content per weight unit (Doughty et al 1991).…”
Section: Change In Sulforaphane Contents During Different Growth and mentioning
confidence: 99%
“…In roots a wide range of GLS concentration (from 1.7 up to 296 μmol/g DW) depending on genotype is reported by several authors (Li and Kushad 2004, Agneta et al 2013, Wedelsbäck Bladh 2014. Besides genotype, sulfur fertilization led to enhanced glucosinolate content in a number of Brassica species, and increases of over 10-fold were reported (Falk et al 2007). On wasabi, whose flavor as for horseradish comes from the liberation of the allyl-isothiocyanate (AITC) by the hydrolysis of precursor SIN, Sultana et al (2002) found that fertilization with ammonium sulphate produced the highest-quality rhizomes with an increase of 72% in AITC yield, while N alone reduced it by up to 15%.…”
Section: Resultsmentioning
confidence: 98%
“…Among agronomic practices, the fertilization has been largely studied in numerous Brassicaceae crops to maximize benefits for production and GLS content. Several studies highlighted that S led to increases of GLS in most cases (Falk et al 2007) while N level, form and application timing exhibited diverse responses. Referring to horseradish, the influence of N and S on GLS content was mostly studied in embryoids, suspension cells and calli, and plantlets grown in vitro; in the latter, Alnsour et al (2012) found that GLS concentrations could be modulated 20-fold by varying the sulphate concentration in the medium.…”
mentioning
confidence: 99%